Semiconducting single-walled carbon nanotubes or very rigid conjugated polymers: a comparison - Zaumseil, Jana (Advanced electronic materials, 2019)
With the ability to produce large amounts of purely semiconducting and even monochiral dispersions of single-walled carbon nanotubes (SWCNT) their application as a bulk material in thin film devices on a large scale becomes feasible. Their physical properties, processing, and final devices are quite similar to those of semiconducting polymers. In the extreme case one may view carbon nanotubes as very long, rigid, and fully conjugated polymers. This analogy raises the question whether the knowledge accumulated over the last two decades of processing and studying conjugated polymers could be transferred to solution-processed nanotube devices. Here, the optical and electronic properties of both materials in solution and in thin films are discussed and compared with a focus on their application in optoelectronic devices. Some striking similarities and common issues are highlighted to show the connection between conjugated polymers and SWCNTs as 1D semiconductors.
First published: 25 November 2018
Gesehen am 29.05.2019